New Antiretroviral Treatment for HIV. Issue 3 (September 2016) - Badowski, Melissa; Pérez, Sarah; Biagi, Mark; Littler, John
Abstract The Joint United Nations Programme on HIV/AIDS (UNAIDS) has set the global goal of ending the AIDS world epidemic by 2030. In order to end this epidemic they have established a 90-90-90 goal to be achieved by 2020, which may be problematic, especially in low- and middle-income countries. This goal includes 90% of individuals with HIV globally being diagnosed, on treatment, and virologically suppressed. Based on global estimates from 2014–2015, approximately 36.9 million individuals are living with HIV. Of those, 53% have been diagnosed with HIV, 41% are on antiretroviral therapy (ART), and 32% have viral suppression with <1000 copies/ml. Comprehensive approaches are needed to improve the number of people living with HIV (PLWH) who are diagnosed, linked, and engaged in care. Once PLWH are retained in care, treatment is key to both HIV prevention and transmission. The development and advancement of new ART is necessary to assist in reaching these goals by improving safety profiles, decreasing pill burden, improving quality of life and life expectancy, and creating new mechanisms to overcome resistance. The focus of this review is to highlight and review data for antiretroviral agents recently added to the market as well as discuss agents in various stages of development (new formulations and mechanisms of action).